GMAT all the verbal - Manhattan Prep (Firm) (2019)
"Manhattan Prep's 99th percentile instructors teach you all of the content and strategies you need to know for the Verbal section of the GMAT"--
Sentence correction. The sentence correction process ; Grammar and meaning ; Sentence structure ; Modifiers ; Parallelism ; Comparisons ; Pronouns ; Verbs ; Idioms -- Reading comprehension. The foundation ; Breaking down the passage ; Mapping the passage ; General questions ; Specific questions ; Extra problem set -- Critical reasoning. Argument structure ; Methodology ; Structure-based family ; The assumption family: find the assumption ; The assumption family: strengthen and weaken ; The assumption family: evaluate the argument and find the flaw ; Evidence family.
DELL
Keywords: Graduate Management Admission Test -- Study guides; Business education -- Examinations, questions, etc; English language -- Grammar -- Examinations, questions, etc; Phrase structure grammar -- Examinations, questions, etc; Problems and Exercises; examination study guides; exercise books; Study guides; Problems and exercises; Examinations